The UTE online judge - Đặng Trường Sơn; Trần Công Tú; Phùng Quang Ngọc (Journal of Technical Education Science, 2012)
Currently, many Vietnamese universities are in the process of building and deploying credit-based curriculums. Typically, the number of credits is reduced to 150, and the self-study hours of students are increased. Teachers and students do not have enough time to meet face to face to discuss programming exercises. This paper proposes the online judge that shortens the evaluative time for the computer programs. The online judge will enable students to practice programming and help teachers assess students’ programs quickly and efficiently. The system can be also used to assess the programming assignments of the homework, the mid-term exams and the final exams.